Pengaruh Konsentrasi HCL dan Lama Perendaman Terhadap Pematahan Dormansi Pada Benih Kopi (Coffea sp.) - Dewi Junita; Hamidan Hamidan; Mawaddah Putri Arisma Siregar; Nana Ariska; Amda Resdiar (Universitas Teuku Umar, 2023)
Research aimed to determine the effect of HCL concentration and soaking time on thebreaking of dormancy in coffee seeds (Coffea sp) and whether or not the interactionbetween the two factors was significant. This research was carried out at the Laboratory and Research Field of the Faculty of Agriculture, Teuku Umar University, Meulaboh, West Aceh from March to April 2020. The materials used in this study were Arabica coffee seeds obtained from Wih Nareh Village, Pegasing District, Central Aceh Regency, a solution hydrochloric acid (HCl), aquades, sandy loam soil. The tools used in this study were 100 ml measuring cup, 40 x 60 cm plastic basket, DJ-A2000 type analytical scale, knife, 1000 ml bottle and camera. The design used in this study was a completely randomized design (CRD) with 4 x 3 factorial pattern with 3 replications. The first factor studied was the concentration of hydrochloric acid (HCL) (K) consisting of 4 levels, namely: K0 = 0% (control), K1 = 1% (1 ml/L water), K2 = 2% (2 ml/L water ) and K3 = 3% (3 ml/L water). The second factor is the immersion time (L) consisting of 3 levels, namely: L1 = 7 hours, L2 = 14 hours and L3 = 21 hours. The parameters studied were growth potential, germination capacity, growth speed, growth synchronously and dormancy intensity. The results showed that the concentration of hydrochloric acid (HCl) had a very significant effect on the germination and growth rate of coffee seeds. However, it did not have a significant effect on growth potential, simultaneous growth, and dormancy intensity. The immersion time did not significantly affect the growth potential, germination rate, growth speed, growth synchronously, and the intensity of dormancy of coffee seeds. There was no interaction between HCL concentration and immersion time on all observed variables..Keywords: Concentration of HCl, Soaking Time, Coffee Seeds